تأثير تمرينات بدنية مصاحبة للموسيقى داخل الماء وخارجه في بعض المتغيرات البدنية والحركية لدى لاعبات كرة القدم الصالات - خضر, أ.م.د رزكار مجيد; عبدالله, أ.م.د نه به ز; عبدالله, الباحثة: فريدة سليم فقى (Sulaimani Journal for Humanities, 2023)
Rhythmic exercises are one of the basic means for the rest of the types of individ ual and group games, due to the specificity of its various exercises and movements and the extent of their impact on the efficiency of the body’s organs. All muscles in the body and increases their flexibility and agility It works on developing physical abilities and skills, as well as developing a sense of movement. The demand for water exercise programs has become increasing due to the diversity of its objectives, including for recreation, treatment and rehabilitation from injuries and recovery by stimulating blood circulation to accelerate the disposal of muscles and tendons from the remnants of exercise fatigue, and that water resistance Usually it is higher than the air resistance and the increased need for stability in certain situations due to the dynamic movement of water requires the participation of a larger number of muscles, and that there are many trainers who consider water training as a multi-faceted form of the training process in a typical and integrated fitness program, unlike many traditional training programs that require training The specifics for each of the components of physical fitness separately in order to affect the various body systems such as the respiratory system and the circulatory system and by using many tools The research aims to discover : The effect of the two training curricula using rhythmic physical exercises, especially in the water and terrestrial medium, on some physical and kinetic variables of female futsal football players. The effect of the two training curricula using rhythmic physical exercises, especially in the water and terrestrial medium, on some skill variables for female futsal football players. The effect of the two training curricula using rhythmic physical exercises, especially within the water and terrestrial medium, on some physical and kinetic variables in the post-test of female futsal football players. In order to verify the objectives of the research, the researcher assumed the following: The two training curricula using rhythmic physical exercises within the water and terrestrial medium positively affect the development of some of the physical and kinetic variables of female futsal football players. The two training curricula using rhythmic physical exercises within the water and terrestrial medium positively affect the development of some of the skill variables of female futsal football players. There are statistically significant differences in the post tests between the two experimental groups that used physical exercises within the water and terrestrial medium in some of the physical, kinetic and skill variables of the female futsal football players. The researcher used the experimental method for its relevance and the nature of the research, and the research community was deliberately identified from the female futsal players in Koya Sports Club for the sports season (2021 - 2022), and the research sample was chosen from this community and its consisted of (16) players representing (72.72%) of the research community. The (22) players were chosen by the random, irregular method, and the players were randomly distributed by lottery into two equal experimental groups, the first group used rhythmic physical exercises within the water medium and the second group used rhythmic physical exercises on the ground, and the number of each group consisted of (8) Female players, and the researcher excluded (4) players who were subjected to the exploratory experiment of physical and skill variables and the training curriculum, and (2) a player due to injury and lack of commitment. The research procedures included building two training curricula based on physical rhythmic exercises inside and outside the water. The second goal was to identify the time taken for each exercise, as well as the rest periods between repetitions and between sets. After that, tribal tests and measurements were conducted, then the two training curricula were implemented by the trainers. The implementation of the curricula took (9) weeks during (3) medium courses and by (3) small courses and by forming a load movement (2:1) in each medium session and by (3) ) Training units in one small session, after which the researcher conducted tests and dimensional measurements with the same procedures and steps that were followed in the tribal tests. The researcher used the following statistical means (arithmetic mean, standard deviation, t-test for related samples, and t-test for independent samples), in addition to the percentage, skew coefficient and change rate (evolution ratio). The researcher reached the following conclusions: Training using rhythmic physical exercises in the water medium had a positive effect on the transitional speed, strength characterized by speed, strength elongation of the abdominal muscles, agility and aerobic capacity. Training using rhythmic physical exercises on the ground had a positive effect on transitional speed and strength, which is characterized by speed, coordination and flexibility. Despite the positive effect that occurred in training using physical rhythmic exercises within the water and terrestrial medium, there was a relative superiority of the rhythmic physical training within the water medium over the rhythmic physical training on the ground in the explosive power of the legs, the speed characteristic of the legs, the strength of the abdominal muscles, agility and aerobic capacity, While there was a relative superiority of the group that used physical rhythmic exercises on the ground on the physical rhythmic training within the water medium in terms of transitional speed, coordination and flexibility. Training using rhythmic physical exercises in the water medium had a positive effect on rolling, damping and short handling skills.